theorem allnth (A: set) (l: nat) {n x: nat}: $ all A l <-> A. n A. x (nth n l = suc x -> x e. A) $;
Step | Hyp | Ref | Expression |
---|---|---|---|
2 |
x IN l <-> E. n nth n l = suc x |
||
3 |
conv lmem |
x e. lmems l <-> E. n nth n l = suc x |
|
4 |
x e. lmems l -> x e. A <-> E. n nth n l = suc x -> x e. A |
||
5 |
A. x (x e. lmems l -> x e. A) <-> A. x (E. n nth n l = suc x -> x e. A) |
||
6 |
all A l <-> A. x (E. n nth n l = suc x -> x e. A) |
||
9 |
A. n A. x (nth n l = suc x -> x e. A) <-> A. x A. n (nth n l = suc x -> x e. A) |
||
11 |
E. n nth n l = suc x -> x e. A <-> A. n (nth n l = suc x -> x e. A) |
||
12 |
A. x (E. n nth n l = suc x -> x e. A) <-> A. x A. n (nth n l = suc x -> x e. A) |
||
13 |
A. n A. x (nth n l = suc x -> x e. A) <-> A. x (E. n nth n l = suc x -> x e. A) |
||
14 |
all A l <-> A. n A. x (nth n l = suc x -> x e. A) |